The role of night shift work on blood pressure among healthy female nurses - Merijanti, Lie T.; Samara, Diana; Tandean, Reza; Harrianto, Ridwan (Universa Medicina, 2008)
Although hypertension is probably the most common disease on earth, little is known about the association between shift work and hypertension. The aim of this study was to determine the relationship of night shift work and blood pressure among healthy nurses. A cross-sectional study was performed from March to April 2007 among 152 healthy female nurses from one hospital in Central Jakarta. Historical data were obtained from a self-administered detailed questionnaire, while anthropometric and blood pressure variables were measured directly. Shift workers had a significantly lower age (29.2 ± 5.6 years) and shorter job experience (6.9 ± 5.9 years) than day workers (age = 36.5 ± 8.7 years; job experience 15.4 ± 8.4 years). There was a higher prevalence of overweight individuals among shift workers (31/43 = 72.1%) in comparison with day workers (12/43 = 27.9%), even though the difference in prevalence did not reach statistical significance (p=0.121). Analysis of covariance yielded a significant relationship between shift work and systolic blood pressure (p=0.046), even after taking into account age and job experience. Systolic blood pressure was significantly influenced by shift working, while diastolic blood pressure was not (p=0.283). Working in the hospital on a 24-hour shift leads to abnormally high systolic blood pressure in female nurses, thus suggesting that this type of work may be a risk factor for cardiovascular disease.